Role of CXCL13 and CCL20 in the recruitment of B cells to inflammatory foci in chronic arthritis - Estefanía Armas-González; María Jesús Domínguez-Luis; Ana Díaz-Martín; Mayte Arce-Franco; Javier Castro-Hernández; Gabriela Danelon; Vanesa Hernández-Hernández; Sagrario Bustabad-Reyes; Alberto Cantabrana; Mariagrazia Uguccioni; Federico Díaz-González (Arthritis Research & Therapy, 2018)
Abstract Background B cells exert their pathogenic action in rheumatoid arthritis (RA) locally in the synovium. This study was undertaken to elucidate the chemokines responsible for the recruitment of B cells in the inflamed synovium, taking into account that the rich chemokine milieu present in the synovial tissue can fine-tune modulate discrete chemokine receptors. Methods Expression levels of chemokine receptors from the CC and CXC family, as well as CD27, were assessed by flow cytometry in CD20+ mononuclear cells isolated from the peripheral blood (PB) and synovial fluid (SF) of RA and psoriatic arthritis patients. Transwell experiments were used to study migration of B cells in response to a chemokine or in the presence of multiple chemokines. Results B cells from the SF of arthritis patients showed a significant increase in the surface expression of CCR1, CCR2, CCR4, CCR5 and CXCR4 with respect to PB. Conversely, SF B cells expressed consistently lower amounts of CXCR5, CXCR7 and CCR6, independent of CD27 expression. Analysis of permeabilized B cells suggested internalization of CXCR5 and CCR6 in SF B cells. In Transwell experiments, CCL20 and CXCL13, ligands of CCR6 and CXCR5, respectively, caused a significantly higher migration of B cells from PB than of those from SF of RA patients. Together, these two chemokines synergistically increased B-cell migration from PB, but not from SF. Conclusions These results suggest that CXCL13 and CCL20 might play major roles in RA pathogenesis by acting singly on their selective receptors and synergistically in the accumulation of B cells within the inflamed synovium.